Therapeutic Drug Monitoring of Long-Acting Rilpivirine and Cabotegravir for Treatment of HIV-1 Infection - A Case Series of Five Patients With One Virologic Failure After Development of Two-Class Resistance - Gerstenberg, Jacob; Klinker, Hartwig; Baier, Michael; Von Braun, Amrei; Seybold, Ulrich; Helbig, Carlotta; Däumer, Martin; Korn, Klaus; Stephan, Christoph; Schleenvoigt, Benjamin T. (Open Forum Infectious Diseases, 2024)
Virologic failure of long-acting rilpivirine/cabotegravir is rare but may result in severely limited treatment options. Known risk factors cannot predict all cases. Therapeutic drug monitoring (TDM) may help identify patients at risk, but reliable thresholds are missing. We report retrospective TDM in a cohort of 5 patients, including 1 virological failure.
CRIS-Team Scopus Importer:2024-10-04
Keywords: cabotegravir; rilpivirine; TDM; two-class resistance; virologic failure